Strategi Pembelajaran Guru PAI dalam Meningkatkan Akhlakul Karimah Siswa - Andi Miftahul Rizkiani Susanti; Asmaji Asmaji; Toha Makhshun (Journal on Education, 2025)
This study aims to determine the learning strategy, describe the noble character, and describe the impact of the learning strategy of Islamic religious education teachers. This study is a qualitative descriptive study using a spiritual, psychological and pedagogical approach. The types of data used are primary and secondary data. Primary data sources come from the principal, vice principal, and Islamic religious education teachers. Secondary data sources come from teacher data, student data and infrastructure data. The main research instrument is the researcher himself then developed using observation guides, interviews and documentation checks. Data processing and analysis techniques go through three stages, namely the process of selecting data, presenting data and drawing conclusions. The results of the study indicate that the Islamic religious education strategy used at MI Asy Syifa Balikpapan is an inquiry, expository, cooperative, affective and problem solving learning strategy, consisting of questions and answers, discussions, lectures, habits, exercises, group work, assignments, punishments and rewards. Description of the noble character of students with assessment indicators, namely religiousness, social discipline, cleanliness, and student responsibility. The impact of learning strategies on students' noble morals is quite good, students begin to be diligent in worship, disciplined, responsible for their relationships and themselves. However, this strategy has not achieved what is expected, so this strategy must be developed by finding learning strategies that can further improve students' noble morals.